The Principle of Freedom in Elections: Interpretation and Correlation with Democratic Governance - Burhanuddin; Maskawati; Wahyu (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2025)
Abstract: This article discusses one of the main principles in the implementation of elections, namely the principle of freedom. This principle is fundamental and serves to ensure the freedom of voters to make their political choices according to the will of the voters and without pressure, intimidation, or intervention from any party. This normative research uses conceptual and legislative approaches. Conceptually analyze the meaning of the free principle and its correlation with the formation of democratic government. The results of the study show that free elections are an absolute requirement for the birth of a democratic government. Intervention in the form of money politics and violations of the neutrality of state apparatus are the main factors that threaten freedom of choice and have the potential to damage the legitimacy of elections. Therefore, the protection of the principle of freedom needs to be strengthened in the legal and institutional framework because it is considered very dangerous for the continuity of democracy and government that is in favor of the people.